2000
DOI: 10.1007/s001340051198
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis in estimating nutritional status and outcome of patients with chronic obstructive pulmonary disease and acute respiratory failure

Abstract: This study suggests that the decrease in BIA-derived ACM is a good indication of malnutrition and of poor outcome in COPD patients with ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 19 publications
0
63
0
6
Order By: Relevance
“…Bioelectrical impedance analysis is a relatively new tool for the assessment of nutrition status; it is useful as diagnostic method both in health and in chronic disease (amyotrophic lateral sclerosis 18 , cirrhosis 25 , hemodialysis 27 , hiv 28 , cancer). An alternative method, bioelectrical impedance spectroscopy, is a technique that measures impedance using 50 or more frequencies; the resulting values are then used to calculate the resistance of the extracellular and intracellular water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioelectrical impedance analysis is a relatively new tool for the assessment of nutrition status; it is useful as diagnostic method both in health and in chronic disease (amyotrophic lateral sclerosis 18 , cirrhosis 25 , hemodialysis 27 , hiv 28 , cancer). An alternative method, bioelectrical impedance spectroscopy, is a technique that measures impedance using 50 or more frequencies; the resulting values are then used to calculate the resistance of the extracellular and intracellular water.…”
Section: Discussionmentioning
confidence: 99%
“…Reactance is the resistive effect produced by the tissue interfaces and cell membranes 25 . Thanks to its potential to detect changes in tissue electrical properties, pa has been found to be an indicator for cell membrane integrity, distribution of water between the intracellular and extracellular spaces, and prediction of body cell mass in various disease conditions [26][27][28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…It is measured by bioelectrical impedance analysis and reflects cell membrane function 15 and indirectly, the body's muscle mass. 16 It is an established parameter for diagnosing malnutrition, and a useful prognostic marker in many clinical conditions 17 including several types of cancer. [18][19][20][21] The Subjective Global Assessment (SGA) questionnaire according to Detsky et al 22 is another means of demonstrating the best combination of sensitivity and specificity in identifying complications related to malnutrition, 23 making the SGA questionnaire a validated tool in cancer patients with which to evaluate nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Faisy et al [4] suggested that BIA might be superior to MAMC in predicting malnutrition and negative outcomes among patients with chronic obstructive pulmonary disease and acute respiratory failure. However, as previously demonstrated, MAMC provides a simple measure of body composition.…”
mentioning
confidence: 99%